Analysis of Ground Water Potential in Gowa Regency, South Sulawesi Province Using the Overlay Method - Rusman Rasyid; Muhammad Arib Musba Amalul Saleh; Nasrul Nasrul (TECHNO: JURNAL PENELITIAN, 2024)
One source of raw water that is often used by humans is groundwater, namely water that occupies cavities in the layers of rock beneath the earth's surface. Groundwater is often used as a source of raw water or a source of clean water by the community apart from river and lake water. Each region has its own level of groundwater potential that can be utilized. The purpose of the analysis carried out is to determine the distribution of potential groundwater in each sub-district area in Gowa Regency through the use of a Geographic Information System (GIS), by applying the overlay method to a number of variables which are factors that influence the presence of groundwater, such as slope, use land, soil type, geology, and rainfall. The results of the analysis that has been carried out show that Gowa Regency has groundwater potential that is spread over each of its sub-districts, where it is divided into a number of potential levels of groundwater availability starting from very low, low, medium, high, and very high.